THE EFFECT OF USING SHORT STORIES THROUGH WATTPAD ON READING COMPREHENSION AT THE TENTH SCIENCE OF MAN 1 METRO - Desti Rahma Pratiwi; Eva Faliyanti (English Education Study Program, 2023)
The aim of this research is to find out the effect of using short stories through wattpad on reading comprehension achievement at the tenth grade science of Man 1 Metro. Wattpad is an application-type social media platform for people who want to read or write stories. This research used quasi experimental design. The subject of this research is the tenth grade science students at Man 1 Metro year 2023. The result data analysis indicates that value t obtained is higher than the value of t table (2.990>2.042). And the significant 0.004 is lower than 0.05. The conclusion is teaching English using short stories through wattpad is effective to increase students’ reading comprehension.